2019
DOI: 10.3390/ma12182855
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ni/Co Mass Ratio on the Microstructure and Properties of Quaternary Cu-Ni-Co-Si Alloys

Abstract: The properties and microstructural evolution of quaternary Cu-Ni-Co-Si alloys with different Ni/Co mass ratios are investigated systematically. These alloys exhibit higher mechanical properties when the Ni/Co mass ratio is 1.12-1.95 (NC-4-NC-5) and show excellent electrical conductivity when the Ni/Co mass ratio is 0.05-0.5 (NC-1-NC-3). With an increase in the Ni/Co ratio, the dimension of precipitated phase continues to increase and the grain size also visibly grows and coarsens. At the same time, the precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…According to the calibration results, the two sets of spots are the same precipitated phase δ-(Ni, Co) 2 Si in the NC-1, NC-2 and NC-3 alloys, with an orthorhombic structure of two variant forms δ 1 and δ 2 . Similarly, the spots in the NC-4 alloy are all the same precipitated phase δ-Ni 2 Si with two variants of δ 1 and δ 2 , which is consistent with the previous results [ 4 , 20 ]. The orientation relationships (ORs) of the precipitates and matrix can be calibrated as (220) Cu //( ) δ1 //( ) δ2 and [ ] Cu //[ ] δ1 //[ ] δ2 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…According to the calibration results, the two sets of spots are the same precipitated phase δ-(Ni, Co) 2 Si in the NC-1, NC-2 and NC-3 alloys, with an orthorhombic structure of two variant forms δ 1 and δ 2 . Similarly, the spots in the NC-4 alloy are all the same precipitated phase δ-Ni 2 Si with two variants of δ 1 and δ 2 , which is consistent with the previous results [ 4 , 20 ]. The orientation relationships (ORs) of the precipitates and matrix can be calibrated as (220) Cu //( ) δ1 //( ) δ2 and [ ] Cu //[ ] δ1 //[ ] δ2 .…”
Section: Resultssupporting
confidence: 91%
“…Combined with previous research, the change of the Ni/Si mass ratio had a strong effect on the microstructure and properties of ternary Cu-Ni-Si alloys [ 18 , 19 ]. A similar method was used to study Cu-Ni-Co-Si alloys and found that different Ni/Co mass ratios also had a great impact on the microstructure and properties of the alloys [ 20 ]. Therefore, it is necessary to further explore the relationship between the internal microstructure and performance of quaternary Cu-Ni-Co-Si alloys to provide more guidance for the subsequent design and development of new alloys.…”
Section: Introductionmentioning
confidence: 99%
“…These precipitates can be confirmed as Ni 2 Si, Co 2 Si or (Ni,Co) 2 Si according to the select area diffraction pattern, as shown in Figure 7b. Based on the literature [26][27][28], the precipitates can be identified as (Ni,Co) 2 Si in the Cu-1.7Ni-1.4Co-0.65Si alloy. When the hot deformation temperature increases to 910 °C, the density of dislocation clearly decreases and dynamic recrystallization occurs, as shown in Figure 8, which can reduce the work hardening [29,30].…”
Section: Microstructure Analysismentioning
confidence: 99%
“…Many factors can affect the mechanical and thermodynamic properties of metal alloys, such as mass ratio, phase composition and grain boundaries. [24][25][26][27] Among these factors, the mass ratio of elements in alloys is fundamental and has a signicant impact on their performance. 24,25 For Mg-Al alloys, some studies on mass ratios have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Among these factors, the mass ratio of elements in alloys is fundamental and has a signicant impact on their performance. 24,25 For Mg-Al alloys, some studies on mass ratios have also been reported. [28][29][30] Using the atomic substitution method, Zhou et al 28 obtained the supercell of Mg 15 Al and studied the mechanical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%